Impact of Flip classroom on performance of MBBS Phase II Students - Kaur, Gagan Deep; Sisodia, Varun; Bhujade, Rashmi; Shikha, Deep; Jain, Pankaj Kumar (Indian Journal of Community Health, 2025)
The majority of Medical Schools are facing issues in providing competency-based education to students. Many students are unable to develop critical thinking and reasoning skills, which are the core of medical education. A flipped classroom is an engaging and modern teaching method. The objectives of the study were: to assess the effectiveness of the flipped classroom strategy towards strengthening knowledge acquisition and retention in community medicine among undergraduate medical students; and to enhance student engagement through active learning. Methodology: This study was conducted in a North Indian medical college among 150 undergraduate students, using a flipped classroom model for teaching the Universal Immunisation Programme (CM10.5). Results: Flipped classroom teaching has aroused the interest of the students, as the attendance of 86.7% students is more than 90%. There is a marked increase in the mean test score of students of each batch after the implementation of the flipped classroom. Nearly 63% of students felt that they were more engaged as learners than in passive teaching. Few teachers (28.5%) believed that it gives extra load to the teachers and are not comfortable in teaching via the Flipped classroom model. Conclusion: Flipped classroom teaching was an effective active learning strategy; larger studies are needed to confirm its impact.